Senses of the word /tɛ̀ː/ in Old Thai (13th – 15th century CE) - Lengwiriyakul, Khet (Journal of Letters, 2024)
Holding an assumption that the word /tɛ̀ː/ in Thai is polysemous and that the word’s senses are historically related, this research intends to conduct a historical study on the word. The purpose of this study is to find out whether /tɛ̀ː/ in the past used to have senses other than the ones existing in the present. This study aims to analyze the senses of /tɛ̀ː/ in Old Thai (13th – 15th century CE) by applying criteria proposed in Tyler and Evans’s Principled Polysemy (Tyler and Evans 2001; Tyler and Evans 2003; Evans 2004; Evans 2005). By applying the criteria, collocates and grammatical constructions are considered in determining the senses of /tɛ̀ː/. The result shows that there were 12 senses of /tɛ̀ː/ in Old Thai, namely: (1) ablative marker of motion, (2) ablative marker of obtainment, (3) ablative marker of achievement, (4) marker of starting time, (5) marker of past time, (6) genitive marker, (7) exclusive marker, (8) topic marker, (9) marker of recipient, (10) marker of beneficiary, (11) marker of abstract goal, and (12) additive conjunction.